Antysemityzm w województwie pomorskim w latach 1920-1939 na przykładzie powiatu toruńskiego i okolic = Anti-Semitism in Pomorskie voivodship in the years 1920-1939. Example : The County Toruń and surrounding area?s - Pielka, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns the problem of anti-Semitism in the interwar period in Pomorskie. For example, which reflects the anti-Semitic phenomena throughout the region, selected Toruń County and neighboring municipalities (Torun was the most important urban center in the province. Pomeranian their headquarters here had Voivod). The text is the fulfillment attempt to fill the gap in research on anti-Semitism in the western part of the Second Polish Republic (in this case the province Pomeranian).
Keywords: Pomorze; antysemityzm; dwudziestolecie międzywojenne; powiat toruński; Pomerania; anti-Semitism; the Toruń County; interwar